A.Complete the table below
![AComplete The Table Below class=](https://ph-static.z-dn.net/files/df0/327f385b674cd0ab105b3f3793715752.jpg)
Answer:
Standard Form:
Values of a, b, c:
Step-by-step explanation:
1.
[tex]2x - 3 {x}^{2} = 5 \\ - 3 {x}^{2} + 2x - 5 = 0 \\ - 1( - 3 {x}^{2} + 2x - 5 = 0) -1 \\ 3 {x}^{2} - 2x + 5 = 0[/tex]
2.
[tex]4 - {x}^{2} = 5x \\ - {x}^{2} - 5x + 4 = 0 \\ - 1( - {x}^{2} - 5x + 4 = 0) - 1 \\ {x}^{2} + 5x - 4 = 0[/tex]
3.
[tex](2x + 5)(x - 4) = 0 \\ 2 {x}^{2} - 8x + 5x - 20 = 0 \\ 2 {x}^{2} - 3x - 20 = 0[/tex]
4.
[tex]2x(x - 1) = 6 \\ 2 {x}^{2} - 2x = 6 \\ 2 {x}^{2} - 2x - 6 = 0[/tex]
5.
[tex](x + 1)(x + 4 ) = 8 \\ {x}^{2} + 4x + x + 4 = 8 \\ {x}^{2} + 4x + x + 4 - 8 = 0 \\ {x}^{2} + 5x - 4 = 0[/tex]